Using text-matching software in educational science research: Research results from 18 universities in Vietnam - Thuan Van Pham; Hien Le Thi Thu; Thanh Thi Nghiem; Hang Do Thi Thu; Can Nguyen Duc; Huy Nguyen Hoa (European Science Editing)
Background: Plagiarism by researchers and college students in Vietnam has become a major concern for publishers. Many cases of master’s theses of graduate students in Vietnam being cancelled or their diplomas being revoked for plagiarism are recorded, and some scientists also have been warned or criticized for plagiarism or self-plagiarism.Objectives: The purpose of this study was to analyse the use in educational research of 13 popular text-matching software packages at universities in Vietnam.Methods: The study was based on semistructured interviews of 104 researchers from 18 universities in Vietnam with reference to the use of text-matching software by the researchers.Results: The three most commonly used text-matching software packages were Turnitin, DoIT, and iThenticate. Three-fourths of the 18 universities employ text-matching software and although 17 out of 104 researchers were unfamiliar with such software. Universities in Vietnam primarily require plagiarism checks for master’s theses (79 out of 104 responses) and doctoral dissertations (72 out of 104 responses). Out of 104 participants, 32 use them for graduate theses or project reports, and 45 use them for research papers and project reports.Conclusions: Many universities in Vietnam are yet to specify the requirements for use of text-matching software, and most researchers and students use it only when prompted by publishers or institutions. Researchers in educational science typically lack the financial resources and the requisite skills for using text-matching software.